Mathematical Analysis and Applications - Hari Mohan Srivastava (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Investigations involving the theory and applications of mathematical analytic tools and techniques are remarkably wide-spread in many diverse areas of the mathematical, physical, chemical, engineering and statistical sciences. In this Special Issue, we invite and welcome review, expository and original research articles dealing with the recent advances in mathematical analysis and its multidisciplinary applications.